2002
DOI: 10.1016/s0735-1097(02)01940-x
|View full text |Cite
|
Sign up to set email alerts
|

Historical criteria that distinguish syncope from seizures

Abstract: A simple point score of historical features distinguishes syncope from seizures with very high sensitivity and specificity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
156
1
4

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 339 publications
(162 citation statements)
references
References 26 publications
1
156
1
4
Order By: Relevance
“…Guidelines now exist that use clinical history alone to distinguish NCS from seizures (94% sensitivity and specificity; Figure 3) or other forms of syncope (89% sensitivity and 91% specificity). 11,12 Despite this, NCS is still commonly mistaken for epileptic seizures even though the conditions rarely coexist in the same patient. 18 Neurocardiogenic syncope is estimated to constitute 6% to 39% of cases of presumed epilepsy depending on the population studied 19 and therefore erroneous diagnosis may lead to inappropriate treatment with social and economic stigmatization.…”
Section: Discussionmentioning
confidence: 99%
“…Guidelines now exist that use clinical history alone to distinguish NCS from seizures (94% sensitivity and specificity; Figure 3) or other forms of syncope (89% sensitivity and 91% specificity). 11,12 Despite this, NCS is still commonly mistaken for epileptic seizures even though the conditions rarely coexist in the same patient. 18 Neurocardiogenic syncope is estimated to constitute 6% to 39% of cases of presumed epilepsy depending on the population studied 19 and therefore erroneous diagnosis may lead to inappropriate treatment with social and economic stigmatization.…”
Section: Discussionmentioning
confidence: 99%
“…j Key words syncope AE diagnosis AE age distribution AE sex AE signs and symptoms syncope [2,15,27]. Therefore, knowledge about the occurrence of triggers, signs, and symptoms provides important background information for physicians to optimize and personalize their diagnostic strategy.…”
Section: Introductionmentioning
confidence: 99%
“…Published studies have found that the electroencephalogram (EEG) is of low diagnostic yield when the clinical diagnosis is syncope [2][3][4][5] . Reviews state that EEGs should not be performed routinely in cases of suspected syncope unless there has been a witnessed seizure 6 , there is a history of prior seizures 7,8 , or there are "symptoms suggestive of a seizure" 7,9 . Electroencephalograms ordered by a neurologist might be expected to have a higher diagnostic yield because most neurologists are experienced in evaluating patients with syncope and seizures, and presumably would only refer a patient with suspected syncope for an EEG if there was something ABSTRACT: Background: Prior studies have shown that the electroencephalogram (EEG) is of low diagnostic yield in the evaluation of syncope but have not looked at the yield according to referring physician specialty.…”
mentioning
confidence: 99%